Inovasi Digital dalam Pengelolaan Keuangan UMKM: Sosialisasi Pencatatan Laporan Keuangan melalui Aplikasi Teman Bisnis - Rosita Farhat; Lilavita Dina Setyawati; Tiska Ayu Mahardika; Mohamad Aziz; Tituk Diah Widajantie (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
This community service aims to help Micro, Small, and Medium Enterprises (MSMEs) improve their financial recording capabilities through the Teman Bisnis application. The research method uses a socialization approach. This socialization activity was carried out at the Dharma Wanita Persatuan (DWP) Regional Revenue Management Technical Implementation Unit (UPT PPD) of Madiun City. The results of the activity showed that the Teman Bisnis application had a positive impact on MSME financial recording. Business actors felt helped in preparing neater and more structured financial reports. However, one of the obstacles found was limited access to premium features that require a subscription fee.